ESPEN guideline on home enteral nutrition. Issue 1 (January 2020) - Bischoff, Stephan C.; Austin, Peter; Boeykens, Kurt; Chourdakis, Michael; Cuerda, Cristina; Jonkers-Schuitema, Cora; Lichota, Marek; Nyulasi, Ibolya; Schneider, Stéphane M.; Stanga, Zeno; Pironi, Loris
Summary: This guideline will inform physicians, nurses, dieticians, pharmacists, caregivers and other home enteral nutrition (HEN) providers about the indications and contraindications for HEN, and its implementation and monitoring. Home parenteral nutrition is not included but will be addressed in a separate ESPEN guideline. This guideline will also inform interested patients requiring HEN. The guideline is based on current evidence and expert opinion and consists of 61 recommendations that address the indications for HEN, relevant access devices and their use, the products recommended, the monitoring and criteria for termination of HEN, and the structural requirements needed to perform HEN. We searched for meta-analyses, systematic reviews and single clinical trials based on clinical questions according to the PICO format. The evidence was evaluated and used to develop clinical recommendations implementing the SIGN method. The guideline was commissioned and financially supported by ESPEN and the members of the guideline group were selected by ESPEN.